1997
DOI: 10.1016/s0022-5223(97)70222-8
|View full text |Cite
|
Sign up to set email alerts
|

Minimal operative mortality in patients undergoing coronary artery bypass with significant left ventricular dysfunction by maximization of metabolic and mechanical support

Abstract: Between January 1, 1992, and January 23, 1996, 111 consecutive patients with severe left ventricular dysfunction underwent isolated coronary artery bypass grafting. The ejection fraction in these patients ranged from 10% to 34% (mean 27.9% +/- 5.4%); in 18 patients the value was less than 20%. The high operative mortality rate (7.6% in Society of Thoracic Surgeons database) in this group of patients at high risk was targeted for reduction by provision of, in addition to the usual inotropic support, progressive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
3

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 28 publications
1
22
0
3
Order By: Relevance
“…Poor or even average results are less likely to be published. Typically the published papers differ from the STS data base from the corresponding time reporting a substantially higher mortality of 7.6% in patients with EF≤0.35 (48). Furthermore, the majority of studies are highly selected case series excluding patients that required valve procedures, redo-procedures, patients with cardiogenic shock and occasionally only including those that hade viable myocardium detected preoperatively or even excluding those that required IABP, had recent preoperative events or died early after surgery.…”
Section: Commentmentioning
confidence: 99%
“…Poor or even average results are less likely to be published. Typically the published papers differ from the STS data base from the corresponding time reporting a substantially higher mortality of 7.6% in patients with EF≤0.35 (48). Furthermore, the majority of studies are highly selected case series excluding patients that required valve procedures, redo-procedures, patients with cardiogenic shock and occasionally only including those that hade viable myocardium detected preoperatively or even excluding those that required IABP, had recent preoperative events or died early after surgery.…”
Section: Commentmentioning
confidence: 99%
“…Administration of T 3 has been proposed to increase cardiac output and to decrease vascular resistance in certain clinical settings when conventional inotrophic drugs prove insufficient (190). Patients with poor ventricular function may benefit the most from the use of T 3 through a reduction in the need for conventional inotrophic drugs (191). Additionally, in the rat postinfarction model of heart failure, treatment with T 4 produced a positive inotrophic response, including an increase in left ventricular conractility and an increase in left ventricular end-diastolic pressure (192).…”
Section: Thyroid Hormone As a Tool In The Therapy Of Cardiovascular Dmentioning
confidence: 99%
“…The longer aortic clamping time and lower ejection fraction in the T group, although not statistically significant (P = 0.083 and 0.099, respectively), raise the possibility that the patients randomly allocated to this group had more complex cardiopathies and that their surgical procedure was more complicated. Other studies demonstrated that T 3 replacement reduced clinical endpoints postoperatively, such as the need for pacemaker and mechanical assistance, use of vasoactive drugs, need for intensive care, or prevalence of atrial fibrillation (8,10,12,15,18), and some studies have even suggested decreased mortality (13,14).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have explored the intravenous administration of T 3 to adults (8)(9)(10)(11)(12)(13)(14) and, more recently, to children (15)(16)(17), during the cardiac surgery postoperative period. The results concerning clinical benefits, actual hemodynamic effects and need for inotropic drugs have been controversial.…”
Section: Introductionmentioning
confidence: 99%